2018
DOI: 10.1016/s0140-6736(18)31320-5
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes

Abstract: Type 1 diabetes is a chronic autoimmune disease characterised by insulin deficiency and resultant hyperglycaemia. Knowledge of type 1 diabetes has rapidly increased over the past 25 years, resulting in a broad understanding about many aspects of the disease, including its genetics, epidemiology, immune and β-cell phenotypes, and disease burden. Interventions to preserve β cells have been tested, and several methods to improve clinical disease management have been assessed. However, wide gaps still exist in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
791
1
27

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,078 publications
(934 citation statements)
references
References 174 publications
13
791
1
27
Order By: Relevance
“…Our finding of DKA being present at diagnosis in a third of patients is in line with previous reports [2]. DKA is a serious clinical problem in newly diagnosed childhood T1D, and our results here show that T1D patients with DKA exhibit significant changes in peripheral blood immune cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding of DKA being present at diagnosis in a third of patients is in line with previous reports [2]. DKA is a serious clinical problem in newly diagnosed childhood T1D, and our results here show that T1D patients with DKA exhibit significant changes in peripheral blood immune cells.…”
Section: Discussionsupporting
confidence: 93%
“…T1D has been classically described as a T cell-mediated disease [2]; however, an increasing number of studies have shown the importance of other immune cells in disease pathogenesis [6,8,9,14]. In the current study, we examined changes in a wide spectrum of immune cells in children with newly diagnosed T1D using unseparated PBMCs staining panels and HIP-C version 3.3 protocol developed by the COST-ENTIRE consortium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 1 diabetes (T1D) is a chronic autoimmune disease characterised by the progressive and insidious destruction of β cells . This disease results from immune system breakdown, which is predominately mediated via T helper 1 (Th1) cells, accompanied by the activation and islet infiltration of immune cells, which collaborate to destroy pancreatic β cells and cause overt hyperglycaemia . Current T1D therapy mainly involves exogenous insulin replacement, highlighting the need for immunotherapies to limit the disease and improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%